Electric Machines : Series 2700 - System Description - Hps SystemTechnik
This system decription describes all machines, offered by hps systemtechnik, wich are used in training system. All electric machine supplied by hps systemtechnik are required with four machines feet. Therefore, bases are not neccessary. Each experimental machine needs only once coupling half for connection to the Brake unit. It is also possible to use machines of other training programs as well as industrial machines. For this, machine feet are available in three different heights. This allows to use existing experimental machines, as well as usual commercial machines, with standard feet and a shaft height of 63 mm, 71 mm and 80mm..